Description of Copra Marketing in Potuho Jaya Village Lalembuu Sub-district, South Konawe District - Dewi Puji Pangestu; Musadar Mapasomba; Sitti Nur Isnian (International journal of technology and education research, 2024)
The research aims to determine the description of copra marketing in Potuho Jaya Village, Lalembuu District, South Konawe Regency at this time. It can be seen from the farmers who have high potential to develop coconut or copra farming, farmers can support copra marketing in Potuho Jaya Village and the consumer side is very supportive of marketing. Meanwhile, the factors that influence copra marketing in Potuho Jaya Village, Lalembuu District, Konawe Selatan Regency include good quality, relatively low prices, purchasing power from Potuho Jaya Village and its surroundings, and the income can be seen from the land area. The more land the farmer owns, the more his income will be